Peningkatan Return on Equity Melalui Firm Size, Sales Growth, Current Ratio, Total Asset Turnover, dan Debt to Equity Ratio - Mutia Rida Utami; Erma Setiawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Return on Equity (ROE) is a financial ratio used to measure a company's ability to generate profits from each unit of equity (own capital) invested by shareholders. The purpose of this study is to examine the impact of firm size (FZ), sales growth (SG), current ratio (CR), total asset turnover (TAT), and debt-to-equity ratio (DER) on return on equity (ROE) in companies engaged in the mining sector and listed on the Indonesia Stock Exchange (IDX) during the period 2021 to 2023. This study uses a quantitative approach with an associative method, which is a method that aims to determine the relationship or influence between two or more variables. Data analysis in this study was carried out using multiple linear regression analysis to measure the magnitude of the influence of each independent variable on the dependent variable. In addition, a classical assumption test was carried out which included normality, multicollinearity, heteroscedasticity, and autocorrelation tests to ensure the validity of the regression model used. Based on the results of multiple linear regression analysis conducted on 13 companies, the descriptive statistical results show that firm size (FZ), sales growth (SG), current ratio (CR), total asset turnover (TAT), and debt to equity ratio (DER) on return on equity (ROE) have no effect whatsoever. Meanwhile, total asset turnover (TAT) is proven to have a significant effect on ROE, with a scale value of 0.000, which is smaller than the limit of 0.05.